Comparison of anterior knee laxity, stiffness, genu recurvatum, and general joint laxity in the late follicular phase and the ovulatory phase of the menstrual cycle - Mayuu Shagawa; Sae Maruyama; Chie Sekine; Hirotake Yokota; Ryo Hirabayashi; Arisa Hirata; Mizuki Yokoyama; Mutsuaki Edama (BMC Musculoskeletal Disorders, 2021)
Abstract Background One risk factor for anterior cruciate ligament (ACL) injury may be fluctuations in female hormones. This study examined variability in joint laxity, as a risk factor for ACL injury, during the menstrual cycle. Methods Subjects were 15 female university students with regular menstrual cycles. We measured estradiol (E2) concentration, anterior knee laxity (AKL), stiffness, genu recurvatum (GR), and general joint laxity (GJL) during the late follicular and ovulatory phases. AKL was measured as anterior tibial displacement of the femur after application of 44-, 89-, and 133-N loads on the tibia. Stiffness was calculated as Δforce/Δdisplacement at loads of 44–89 N and between 89 and 133 N. GR was measured prone, with the base of the patella distal to the edge of the bed. The University of Tokyo joint laxity test was used to evaluate GJL. Results E2 concentration was significantly higher in the ovulatory phase than in the late follicular phase (p = 0.018), AKL and stiffness did not differ significantly between phases, and GR and GJL were significantly higher in the ovulatory phase than in the late follicular phase (p = 0.011, 0.031). Conclusion These findings suggest that E2 concentrations may affect GR and GJL during the menstrual cycle.